2015
DOI: 10.1021/acs.jctc.5b00866
|View full text |Cite
|
Sign up to set email alerts
|

Heuristics-Guided Exploration of Reaction Mechanisms

Abstract: For the investigation of chemical reaction networks, the efficient and accurate determination of all relevant intermediates and elementary reactions is mandatory.The complexity of such a network may grow rapidly, in particular if reactive species are involved that might cause a myriad of side reactions. Without automation, a complete investigation of complex reaction mechanisms is tedious and possibly unfeasible. Therefore, only the expected dominant reaction paths of a chemical reaction network (e.g., a catal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
218
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(218 citation statements)
references
References 86 publications
0
218
0
Order By: Relevance
“…In this work, we have demonstrated that the automated reaction path search algorithm on the basis of the GRRM strategy combined with the mixed‐spin potential energy surface is useful by taking the series of M + + OCS (M denotes 3 d transition metal from Sc to Cu) reactions as examples. As mentioned in Introduction, other automated reaction path search methods have been recently developed . It would be easy to apply the mixed‐spin potential energy surface scheme to such newly‐developed methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we have demonstrated that the automated reaction path search algorithm on the basis of the GRRM strategy combined with the mixed‐spin potential energy surface is useful by taking the series of M + + OCS (M denotes 3 d transition metal from Sc to Cu) reactions as examples. As mentioned in Introduction, other automated reaction path search methods have been recently developed . It would be easy to apply the mixed‐spin potential energy surface scheme to such newly‐developed methods.…”
Section: Discussionmentioning
confidence: 99%
“…Reaction path search techniques combined with quantum chemical calculations, which can automatically explore important reaction pathways on the multi‐dimensional potential energy surfaces, are very useful for understanding detailed reaction mechanisms. Recently, various automated reaction path search algorithms have been proposed . For example, Maeda and coworkers developed the scaled hypersphere search algorithm and artificial force induced reaction method to find transition states and thus reaction pathways in an automated way without intuition.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the configuration space can become very large, computational costs of carrying out first‐principles calculations grow rapidly. As a result, they cannot be performed for every intermediate in large reaction networks . This issue can be overcome by the application of a reactive force‐field .…”
Section: Introductionmentioning
confidence: 99%
“…From these potential energy surface characterizations, one can qualitatively understand the mechanisms of a chemical reaction . Recently, automated reaction path searches using various computational algorithms are becoming useful tools, which enable identification of energetically important reaction pathways on the potential energy surface directly obtained from quantum chemistry calculations . For example, Maeda and Ohno have developed a powerful and automated scaled hypersphere search algorithm implemented in the GRRM (Global Reaction Route Mapping) computer code, which has been interfaced with various quantum chemistry software packages.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it should be mentioned that efficient reaction path search algorithms on the basis of string method, including the single‐ended growing string method and freezing string method, have also been developed . These newly developed algorithms have been benchmarked and applied to a large number of chemical reaction systems to understand the detailed mechanisms, kinetics and dynamics . According to the most recent computational work, the string methods are found to be more efficient than AFIR for atmospheric and combustion reaction systems …”
Section: Introductionmentioning
confidence: 99%